Adult living donor liver transplantation from donors with Gilbert's syndrome: Is it safe?. Issue 9 (15th July 2020) - Akyildiz, Murat; Gungor, Gokhan; Guler, Necdet; Acar, Sencan; Erdogan, Yalcin; Gencdal, Genco; Dayangaç, Murat; Tokat, Yaman
Abstract: Backgrounds: We evaluate whether it is safe to accept donors with Gilbert's syndrome (GS) for a living donor liver transplantation (LDLT) or not. This study is the first controlled study to be conducted. Methods: Between January 2004 and May 2014, 600 LDLTs which used right lobe liver grafts were performed in our center. Forty‐five of the 600 donors had a GS diagnosis. For a control group, 99 donors without GS who had completed 1 year or more of follow‐up were selected retrospectively and consecutively. The clinical results of the donors and recipients were then analyzed. Results: A total of 45 donors with GS and 99 donors without GS were included. There were no significant differences in patient demographics, actual graft weight, remnant ratio, portal and ductal variations, pre‐peri‐post–operative liver enzymes. The donors with GS had significantly higher bilirubin levels compared with the control group at first reading, at maximal peak, and post‐operative 1‐7 days, 1st and 6th months ( P < .001 for all readings). Post‐operative complication ratio was 40% in GS, 34.3% in non‐GS group. In GS and non‐GS group, hospitalization period was 10.2 and 9.2 days, respectively. The 1‐year donor survival rate was 100% for both groups and 1‐year recipient survival was similar who have donors with GS and non‐GS (93.3%; 92.9%, P = .93). Conclusions: The use of right lobe grafts from donors with GS appears to be safe for donor health.